Performance assessment of a 619kW photovoltaic power plant in the northeast of peninsular Malaysia - M. Nirrmahl Raj; Jagadeesh Pasupuleti (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Photovoltaic (PV) power plants are becoming widely implemented and in larger scale around the world. Understanding performance criteria is crucial in the benchmark of PV plants and ascertaining performance requirements during both design and operational stage of a PV plant. performance ratio (PR) and capacity factor (CF) are two generally accepted benchmarks for the assessment of a grid connected PV plant. However, within the South East Asia region, and especially within Malaysia, there is a lack of compilation and benchmark for the PR and CF values of existing and operational PV plants. This lack of data is disadvantageous for the designing and assessment of performance of any PV plants in the area. Thus, the focus of this study is to assess the PR and CF performance a 619kW PV plant in the Northeast of Peninsular Malaysia, with the ultimate goal of proposing a standard. From the continuous operation of the said PV plant for the duration of one year, the plant energy production has been obtained and is compared with the simulated energy generation model. Based on the comparison, the plant is determined to be operating with PR value of 0.77 and CF value of 12%. The plant is evaluated to be operating within benchmark values. These values not only verify the performance of the studied PV plant, they also present a form of comparison for future studies.